Analyses of the Iridoid Glucoside Dimers in Paederia scandens Using HPLC–ESI–MS/MS. Issue 4 (21st February 2013) - Lu, Chen‐Ceng; Wang, Jian‐Hua; Fang, Dong‐Mei; Wu, Zhi‐Jun; Zhang, Guo‐Lin
Abstract Introduction Many dimers consisting of structurally similar monomers are difficult to be identified even using NMR. Rapid structural identification of iridoid glycoside dimers, especially isomeric dimers in a complicated matrix, remains desirable. Objective To develop a rapid, sensitive analytical method for structural elucidation of trace iridoid glycoside isomers in a complicated extract. Methods Three isomeric iridoid glucoside dimers, paederoscandoside, saprosmoside E and saprosmoside D, were isolated and further analysed by electrospray ionisation quadrupole time‐of‐flight tandem mass spectrometry (ESI–QTOF–MS/MS) in positive‐ion mode. Energy‐resolved mass spectrometry (ERMS) was used to provide information on the relative intensity of ions versus collision energy. The crude extract of Paederia scandens was analysed by HPLC–ESI–MS/MS. Results The relative abundance of product ions in the MS/MS spectra from ammonium adduct ions varied greatly for the three isomers. The energy‐resolved experiments enhanced differences among the three isomers. A total of 13 iridoid glucoside dimers (three groups of isomers) in the extract of P. scandens were identified or tentatively characterised by using HPLC–ESI–QTOF based on the tandem mass spectra of references. Conclusion Linkage sites between different hydroxyl groups on the sugar and carboxyl groups for the three groups of isomers are confirmed. The reason for fragmentation differences might be that cleavage of the glycosidic bond accompanies the active H in vicinal hydroxyl rearrangement. The MS method is a useful tool for the analysis of isomers, especially trace isomers in a complicated extract. Copyright © 2013 John Wiley & Sons, Ltd.